2018
DOI: 10.1177/0193841x18786818
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Scale-Up of an Evidence-Based Intervention: A Case Study

Abstract: Policy makers face dilemmas when choosing a policy, program, or practice to implement. Researchers in education, public health, and other fields have proposed a sequential approach to identifying interventions worthy of broader adoption, involving pilot, efficacy, effectiveness, and scale-up studies. In this article, we examine a scale-up of an early math intervention to the state level, using a cluster randomized controlled trial. The intervention, Pre-K Mathematics, has produced robust positive effects on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Examples of interventions include the preschool Promoting Alternative Thinking Strategies (PATHS) curriculum, which focuses on children’s problem solving skills, emotional awareness, social-emotional skills and self-control (Greenberg and Kusche, 1993; Kam et al, 2003; Domitrovich et al, 2007). There are also interventions that focus explicitly on improving preschoolers’ early math that have been shown to be effective such as Pre-K Mathematics (Starkey et al, 2004; Thomas et al, 2018) and Building Blocks (Clements and Sarama, 2007; Clements and Sarama, 2011). Finally, interventions designed to promote preschoolers’ emergent literacy have shown positive effects (Justice and Pullen, 2003; Farver et al, 2009; Justice et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of interventions include the preschool Promoting Alternative Thinking Strategies (PATHS) curriculum, which focuses on children’s problem solving skills, emotional awareness, social-emotional skills and self-control (Greenberg and Kusche, 1993; Kam et al, 2003; Domitrovich et al, 2007). There are also interventions that focus explicitly on improving preschoolers’ early math that have been shown to be effective such as Pre-K Mathematics (Starkey et al, 2004; Thomas et al, 2018) and Building Blocks (Clements and Sarama, 2007; Clements and Sarama, 2011). Finally, interventions designed to promote preschoolers’ emergent literacy have shown positive effects (Justice and Pullen, 2003; Farver et al, 2009; Justice et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We provided minimal extra support and monitoring during the implementation, which mimicked how the program is implemented when schools use it outside the study. We expect this feature to result in smaller effect sizes (see e.g., Thomas et al, 2018, for an interesting discussion and results in line with this hypothesis). All comparison studies monitor and support their tutors more than we do or have personnel hired by the study that perform the intervention.…”
Section: Study Design and Effect Sizesmentioning
confidence: 72%
“…The intervention we examine is Pre-K Mathematics, a supplementary math curriculum for use with economically disadvantaged preschool children. The program, recently described in Thomas, Cook, Klein, Starkey, and DeFlorio (2018), combines a developmentally sequenced curriculum of small-group math activities with concrete manipulatives that teachers implement in the classroom in order to improve skills in numbers, operations, geometry, pattern knowledge, and informal measurement. To improve fidelity and dosage, teachers receive professional development first through workshops and then through in-class coaching.…”
Section: Methods the Rctmentioning
confidence: 99%
“…The ultimate goal is to prepare children for standards-based math instruction in kindergarten. The What Works Clearinghouse (2013) rates Pre-K Mathematics as an effective evidence-based program, and several more recent RCTs have shown that its improvements in math performance are of at least moderate effect size (Thomas et al, 2018).…”
Section: Methods the Rctmentioning
confidence: 99%
See 1 more Smart Citation